2009
DOI: 10.1051/0004-6361/200912736
|View full text |Cite
|
Sign up to set email alerts
|

The onset of solar cycle 24

Abstract: We study the response of the low-degree, solar p-mode frequencies to the unusually extended minimum of solar surface activity since 2007. A total of 4768 days of observations collected by the space-based, Sun-as-a-star helioseismic GOLF instrument are analyzed. A multi-step iterative maximum-likelihood fitting method is applied to subseries of 365 days and 91.25 days to extract the p-mode parameters. Temporal variations in the l = 0, 1, and 2 p-mode frequencies are then obtained from April 1996 to May 2009. Wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
85
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(102 citation statements)
references
References 20 publications
15
85
2
Order By: Relevance
“…While the frequency shifts were proven to be closely correlated with the surface activity proxies over the last three solar cycles (21, 22, and 23) (e.g., Chaplin et al 2007b), clear differences were recently shown between the global p-mode frequencies and the surface activity of the Sun during the unusually extended minimum of cycle 23 (Broomhall et al 2009;Salabert et al 2009;Tripathy et al 2010). Furthermore, a faster cyclic frequency variations, with a period of about 2 years, was observed to coexist in the Sun (Benevolenskaya 1995;Fletcher et al 2010), which is believed to have an origin located deeper inside the convective zone.…”
Section: Introductionmentioning
confidence: 98%
“…While the frequency shifts were proven to be closely correlated with the surface activity proxies over the last three solar cycles (21, 22, and 23) (e.g., Chaplin et al 2007b), clear differences were recently shown between the global p-mode frequencies and the surface activity of the Sun during the unusually extended minimum of cycle 23 (Broomhall et al 2009;Salabert et al 2009;Tripathy et al 2010). Furthermore, a faster cyclic frequency variations, with a period of about 2 years, was observed to coexist in the Sun (Benevolenskaya 1995;Fletcher et al 2010), which is believed to have an origin located deeper inside the convective zone.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore the investigation will also be important to check the possibility of using the solar cycle changes induced in the p-mode parameters as precursors of solar activity. We hope to extend this analysis during the peculiar extended minimum of activity cycle 23, in which some frequency shifts are not following the traditional activity indexes (Broomhall et al 2009;Salabert et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The understanding of the origin of low-frequency acoustic absorption and high-frequency acoustic enhancement is of particular interest nowadays, due to the possibility to use the induced solar cycle changes on p-mode parameters as precursor of solar activity. Acoustic waves seem indeed to undergo substantial changes before the appearance of macroscopic structure at the solar surface Howe et al 2009;Salabert et al 2009). Therefore to correctly use the p-mode solar cycle changes as a precursor of activity it is extremely important to understand their origin and link them to the specific magnetized areas.…”
Section: Leaking Fast and Slow Mhd Waves To Magnetic Featuresmentioning
confidence: 99%
“…The upper limit on the frequency range (i.e., 3.71 mHz) was determined by how high in frequency the data could be fitted before errors on the obtained frequencies became too large due to increasing line widths causing modes to overlap in frequency. Figure 2 shows mean frequency shifts of the p modes observed by BiSON (also see Broomhall et al 2009;Salabert et al 2009;Fletcher et al 2010). A scaled version of the 10.7 cm flux is also plotted in Figure 2.…”
Section: Determining Variations In P-mode Frequencies Throughout the mentioning
confidence: 99%